Bit Plane Based Image Authentication in Spatial Domain - Das, Sujit; Mandal, Jyotsna Kumar; Bhowal, Arundhati (International Journal of Computer Sciences and Engineering, 2025)
In this paper a corelated bit plane based steganographic technique has been proposed. The image is sliced into bit planes. A weighted matrix is created corresponding to each bit plane. The entries in the weighted matrix is made based on the position of bit plane and the values are corresponding to ones in bit plane matrix. The correlation of original image and all the weighted matrices corresponding to all bit planes are calculated and bit planes corresponding to two minimum correlation coefficients are selected for embedding. The secret image is converted into binary string. A window is swept over the selected bit planes in row major non-overlapping fashion and secret bits are embedded into these windows in diagonal fashion. The proposed method achieved better image quality on embedding